International Students’ Perceptions of Race and Socio-Economic Status in an American Higher Education Landscape - Ritter, Zachary S. (Journal of International Students, 2016)
International students add a great deal of cultural and intellectual diversity to college campuses, but they also bring racial stereotypes and socio-economic status hierarchies that can affect campus climate. Forty-seven interviews with Chinese, Japanese, and South Korean international students were conducted. Results indicated that a majority of students had racial and status hierarchies and harbored prejudices toward African-Americans and Southeast Asians. Perceptions of Asian-Americans were mixed. Negative perceptions of Latinos were learned in the U.S., however positive perceptions of Latinos were held by South Korean students who had lived in the U.S. longer. This status hierarchy correlated closely with a racial hierarchy. A lack of opportunities to interact with diverse students led to stereotype proliferation. More policies and programs must be created that reduce misunderstandings between international and domestic students.